2020
DOI: 10.4236/jwarp.2020.121004
|View full text |Cite
|
Sign up to set email alerts
|

Water Hyacinth Control by Glyphosate Herbicide and Its Impact on Water Quality

Abstract: The aim of this study was to evaluate the herbicide glyphosate under aquatic environment conditions, in a controlled and closed experimental field, in the management of water hyacinth (Eichhornia crassipes) in reservoirs. Twenty reservoirs (polyethylene water tanks) with storage capacity of 1000 liters were used, without water flow and without evapotranspired water replacement (worst case), being 04 for each treatment. The adult plants were placed in the water tanks to provide 90% surface occupation of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…In this way, other herbicides have been evaluated for this purpose, and therefore, it is necessary to assess the toxicity to aquatic communities for future use as alternative herbicides. Reglone® (Pitelli et al 2011), Arsenal® NA and Roundup® (Carvalho et al 2005), and Roundup Transorb® (Souza et al 2020) analysis must be performed in different developmental stages to identify the most sensitive to the herbicide and which herbicide is the most toxic to a specific species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, other herbicides have been evaluated for this purpose, and therefore, it is necessary to assess the toxicity to aquatic communities for future use as alternative herbicides. Reglone® (Pitelli et al 2011), Arsenal® NA and Roundup® (Carvalho et al 2005), and Roundup Transorb® (Souza et al 2020) analysis must be performed in different developmental stages to identify the most sensitive to the herbicide and which herbicide is the most toxic to a specific species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these herbicides not being allowed by Brazilian law for aquatic use, the hypothetical concentrations of these herbicides would make the active ingredients reach levels in the water higher than the allowed Brazilian MPL for glyphosate. Souza et al (2020) experimentally used Roundup Transorb® (the same formulation used in this work) to control aquatic plants, applying 7.0 L per ha or 3360 g of acid equivalent per ha in reservoirs with and without Eichhornia crassipes. It was verified that the half-life of glyphosate in water from reservoirs with the plants was 11 days and without the plants was 21 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genus: Cercospora Species: N. eichhorniae that herbicides such as 2,4-D, diquat, paraquat, and glyphosate have resulted in successful control in small, single-purpose water systems such as irrigation canals and dams of around 1 ha in size. However, Souza et al (2020) reported that the use of glyphosate herbicide at its highest recommended dose of 7.0 L ha −1 or 3,360 g of acid equivalent per ha, showed a low potential of environmental impact in the control of WH in reservoirs, but it should be used properly in specific infested sites and never in overall application to the whole infested area. In addition, an integrated approach with other control methods is recommended and seems to be unavoidable in certain circumstances.…”
Section: Genus: Orthogalumnamentioning
confidence: 99%
“…Several studies have been done on eradication, management and control of E. crassipes. The use of glyphosate herbicides, for instance, has been applied in Brazil and the USA with little success [9,10]. Nevertheless, positive results were recorded with the use of weevils for biocontrol of E. crassipes but after a long period [11].…”
Section: Introductionmentioning
confidence: 99%